Antiepileptic Activity of Unmadgajakesari – A Herbomineral Formulation: An Experimental Evaluation - Rajeeta Joseph; Vijaya Pandit; Asmita Wele; Gourav Deshmane (International Journal of Phytomedicine, 2015)
Epilepsy is the most common chronic neurological disorder characterized by episodes of recurrent unprovoked seizures Unmadgajakesari(UGK) is a herbomineral formulation claimed to be useful in epilepsy in traditional medicine. Lack of scientific evidence of UGK for its use in epilepsy lead to the objective of the present work. To evaluate the antiepileptic activity of Unmadgajakesari in animal models After doing the acute toxicity study of UGK, it was evaluated for its antiepileptic activity in Maximal Electroshock(MES) and Pentylenetetrazole(PTZ) induced seizures models in albino wistar rats. For each study animals were divided into 6 groups, each group comprising of 6 animals . Group I –Normal control, Group II-Vehicle control(ghrita), Group III- Drug control(positive control). In test groups(IV-VI) UGK was administered in doses of 70, 140 and 280mg/kg orally for 8days. Antiepileptic activity was evaluated on day 1and 8. UGK was found to be nontoxic upto dose of 2000mg/kg. Significant antiepileptic activity was observed in both the groups on 8th day of UGK administration. In the MES model, significant abolition of tonic hind limb extension was observed in dose of 280mg/kg. In PTZ model, UGK was most effective in the dose of 70mg/kg in delaying the onset and reducing the severity of clonic convulsions. No adverse effects or mortality was seen in this study. UGK appears to have significant antiepileptic activity after repeated administration. With wide spectrum of action, this drug may be useful addition to antiepileptic agents.